The valuation of structured products in Portugal: what was the impact on the products’ pricing after the CMVM’s protocol came into force in 2014? - Oliveira, Catarina Isabel dos Santos (2021)
The structured products market has been growing in the last few years, leading to an increase of the researches in this area. The investigators’ findings in some markets such as United States of America, Germany and Swiss revealed an overpricing trend in the charged prices by the banks. Contributing to this trend is the fact of the payoff structures of these products be very complex, demanding a high financial knowledge by the investors in order to fully understand them. In Portugal, due to the increase in the number of the investors complaints that accuse the financial institutions of lack of transparency in the crisis period, Comissão do Mercado de Valores Mobiliários (CMVM) signed a protocol with nineteen different banks operating in Portugal. This protocol aims to protect the investors interests, guarantying that all the information about the products and their risks is transmitted by the bank, and not selling the riskier products to the retail investors. Thus, the main objective of this dissertation is to understand if the implementation of the protocol had any impact on the products overpricing generally observed in this market, in the perspective of protecting the investors interests. To accomplish this purpose, we use Monte Carlo simulation assuming the Geometric Brownian Motion to simulate the underlying assets price, that will influence the payoff’s product.